An Example of Non-Wood Forest Products in Turkey: Production of Pine Nuts - COŞKUN, Mücahit; GÖK, Mesut; COŞKUN, Sevda (Journal of Forests, 2017)
Turkey is an important country in terms of forestry and biodiversity. In the world, it is one of the places with the highest plant diversity after the equatorial region. There are nearly 4000 endemic plant species. Local conditions have a significant share in the formation of this property. Turkey holds a good position as a wood producer in the production of forest products, which are among forest assets. However, despite its high potential for production of non-wood forest products, which are also among forest assets, it cannot take due advantage of this potential in resource management. Production and marketing problems are the main factors underlying its failure to use this potential. This study aims to draw attention to the production and marketing of pine nuts, which are non-wood forest products, and to put forward suggestions for the use of the above-mentioned potential. Systematic approach was used as a research method. In some cases, regional approaches were also utilized. The data of the Turkish Statistical Institute was used as research material. ArcGIS 10.3 package was utilized in the preparation of cartographic materials. The seed obtained from the cones of Pinus pinea (Stone pine) is a product which is traded both in Turkey’s domestic market and exported abroad. The seeds, which are commercially important, are important sources of income for rural areas. Turkey is suitable for the ecological conditions of Pinus pinea, which is among the industrial wood and non-wood forest products. For this reason, Pinus pinea fields should be made widespread in order to retain population in rural areas and increase their income.